2013
DOI: 10.1371/journal.pone.0066097
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Amyloid Pathology in Transgenic ArcAβ Mice Using Multi-Parametric Magnetic Resonance Imaging

Abstract: Magnetic resonance imaging (MRI) can be used to monitor pathological changes in Alzheimer's disease (AD). The objective of this longitudinal study was to assess the effects of progressive amyloid-related pathology on multiple MRI parameters in transgenic arcAβ mice, a mouse model of cerebral amyloidosis. Diffusion-weighted imaging (DWI), T1-mapping and quantitative susceptibility mapping (QSM), a novel MRI based technique, were applied to monitor structural alterations and changes in tissue composition imposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 49 publications
(76 reference statements)
10
35
1
Order By: Relevance
“…Susceptibility map reconstruction issues similar to those observed in the present work with the traditional physical model (Figures and ) may be found also in published rodent work by other authors. For example, susceptibility contrast was absent from the frontal horn of the lateral ventricles on all in vivo images presented by O'Callaghan et al (Figures and therein), Ziser et al (Figures and therein) and Vaas et al (Figure therein), as well as studies to which we have contributed …”
Section: Discussionsupporting
confidence: 54%
“…Susceptibility map reconstruction issues similar to those observed in the present work with the traditional physical model (Figures and ) may be found also in published rodent work by other authors. For example, susceptibility contrast was absent from the frontal horn of the lateral ventricles on all in vivo images presented by O'Callaghan et al (Figures and therein), Ziser et al (Figures and therein) and Vaas et al (Figure therein), as well as studies to which we have contributed …”
Section: Discussionsupporting
confidence: 54%
“…Aging per se unfolds over time and to the best of our knowledge, inference about age associations of estimates of human brain iron, rely solely on cross sectional studies, while longitudinal studies have been performed only in rodents (Klohs et al, 2013). Cross-sectional design relies on age-related differences between persons that are captured in a snapshot frozen in time, and cannot measure the true dynamic trajectories within a person.…”
Section: Discussionmentioning
confidence: 99%
“…Despite focusing our attention on the lower cortex and corpus callosum, T 1 values were not significantly different between 5-month-old 5xFAD and WT mice. Other studies have found no T 1 differences between AD and WT mice, for example, in PS/APP mice 16–23 months old [34], and in ArcAβ mice, which have similar T 1 values to WT mice irrespective of age [35]. It is not known, however, if the lack of T 1 change in those studies is due to the size and placement of ROIs or the use of different AD transgenic models.…”
Section: Discussionmentioning
confidence: 99%